Analysis of Phenolics, Flavonoids Content, Antibacterial, Antioxidant Properties of Honey and Propolis Samples - Bashyal, Shanta; Rana, Shanti; Rajbhandari, Meena (Amrit Research Journal, 2024)
Honey and propolis are the insect based natural products used to treat various diseases. This study is focused on the analysis of phytochemicals in honey and propolis samples and evaluation of their antioxidant and antibacterial activities. Different extracts of propolis were prepared. Total phenolic and flavonoid content as well as DPPH radical scavenging and antibacterial activities were measured. In screening tests, only phenolics were detected in honey samples while both phenolics and flavonoids were detected in propolis extracts so their content were estimated. In honey samples, total phenolic content varies from 5.802±0.234 to 13.990±0.318 mg GAE/100 g of honey. In propolis samples, total phenolic content varies from 1.59±0.02 (EtOAc extract of PPW) to 38.34±1.04 (MeOH extract of PGW) mg GAE/100 g dry extract. Similarly, total flavonoid content varies from 22.40±2.27 (EtOAc extract of PGS) to 80.61±5.39 (EtOAc extract of PPW) mg QE/100 g dry extract. In antioxidant assay, both honey samples showed DPPH radical scavenging activity at higher concentrations than the propolis samples. Only the ethyl acetate extract of PPW and methanol extracts of PGS and PGW showed activity against S. aureus in antibacterial assay.